Traditional Knowledge in Bivalve Fishery of North Konkan Coast of Maharashtra, India. - Metar, S.Y.; Nirmale V.H.; Gangan, S.S.; Chogale, N.D.; Pai, R.; Bhosale B.P. (Journal of Indian Fisheries Association, 2020)
Traditional knowledge is local knowledge existing within and developed around the specific conditions of women and men, indigenous to a particular geographic area. Fishers' have developed and maintained this knowledge by virtue of their close interaction with natural environment. Study of traditional knowledge will help in pinpointing essential research needs. North Konkan Coast of Maharashtra is dotted by a number of estuaries supporting bivalve fishery. The present study was conducted to document the traditional knowledge of the fishers engaged in the bivalve fishery practiced in the region. A total of 116 fishermen constituted the sample. The data were gathered through personnel interview with semi-structured questionnaire and non-participant observation methods. Fishers were observed to be eﬀectively using traditional wisdom in managing the bivalve fishery with respect to identification of important species, their habitat, preferred time for fishing, methods of exploitation, processing, eﬀect of abiotic factors, etc. The data documented by this study will help academicians, and policymakers for the eﬀective management and conservation of bivalve fishery along the North Konkan coast of Maharashtra.